Isogeometric analysis of free vibration of framed structures: comparative problems. Issue 2 (18th April 2017) - Rauen, Mateus; Machado, Roberto Dalledone; Arndt, Marcos
Abstract : Purpose: The purpose of this paper is to check the efficiency of isogeometric analysis (IGA) by comparing its results with classical finite element method (FEM), generalized finite element method (GFEM) and other enriched versions of FEM through numerical examples of free vibration problems. Design/methodology/approach: Since its conception, IGA was widely applied in several problems. In this paper, IGA is applied for free vibration of elastic rods, beams and trusses. The results are compared with FEM, GFEM and the enriched methods, concerning frequency spectra and convergence rates. Findings: The results show advantages of IGA over FEM and GFEM in the frequency error spectra, mostly in the higher frequencies. Originality/value: Isogeometric analysis shows a feasible tool in structural analysis, with emphasis for problems that requires a high amount of vibration modes.